Analyses of ‘spatial envelope’ rainfall intensity‐duration‐frequency (IDF) curves for Singapore - Wong, Daniel Zi Jian (2015)
The purpose of this study is to analyse the spatial distribution of rainfall in Singapore, through the derivation of intensity-duration-frequency (IDF) curves. These curves were generated using the Gumbel distribution and the log-Pearson type III distribution. From these, five different sets of curves were derived. The Gumbel distribution was use to derive the IDF curves for the whole of Singapore, the Central watershed, the Eastern watershed, the Western watershed and the maximum envelope. The log-Pearson type III was only used to obtain the IDF curves for the whole of Singapore. The results were then used to investigate any possible relationships between spatial rainfall pattern and flooding occurrences, and significance on drainage design. From the results, it was observed that spatial rainfall distribution did not appear to have a significant impact of flood locations. Areas with the largest rainfall intensities over longer durations did not correspond with major flooding incidents. However, the study also noted that different areas of Singapore experienced different rainfall patterns. This means that the current practice of using only one common set IDF curve to design drains in different parts of Singapore may result in over or under-designing.